Influence of Mg2+ ions on the interaction between 3,5-dicaffeoylquinic acid and HTLV-I integrase - Orlando Acevedo; Yesid Cuesta-Astroz; Juvenal Yosa Reyes; Ángela Peña,; Jesús Felipe García-Vallejo (Universitas Scientiarum)
Using molecular simulation, we studied the influence of Mg2+ ions on the binding mode of HTLV-I Integrase (IN) catalyticdomain (modeled by homology) with the 3,5- Dicaffeoylquinic Acid (DCQA). HTLV-I Integrase homology model was built usingtemplate-like crystallographic data of the IN catalytic domain solved for Avian Sarcoma Virus (VSA, pdb: 1VSD). Materials andmethods. In order to analyze the role of Mg2+ in the interaction or coupling between 3,5-DCQA and Integrase, three models were created:i) in the absence of Mg2+ ions, ii) with a Mg2+ ion coordinated at Asp15 and Asp72 and iii) model with two Mg2+ ions coordinated atAsp15-Asp72 and Asp72-Glu108. Coupling force and binding free energy between 3,5-DCQA and HTLV-I IN were assessed in the threemodels. Results. The lowest docking score and free energy binding were obtained for the second model. Mg2+ ion strongly affected thecoupling of the inhibitor 3,5-DCQA with HTLV-I catalytic domain of Integrase, thus revealing a strong interaction in the ligand-proteincomplex regardless of the ligand-catalytic interaction sites for all three models. Conclusion. Altogether, these results strengthen thehypothesis that the presence of one Mg2+ ion could enhance the interaction in the complex by decreasing free energy, therefore increasing the affinity. Moreover, we propose 3, 5-DCQA as an important pharmacophore in the rational design of new antiretroviral drugs.